Land Suitability Study For Oil Palm Plantations On The Politani Samarinda Oil Palm Experimental Garden Land - Laode Muh Asdiq Hamsin Ramadan; Kiamah Fathirizki Agsa Kamarati; Erna Rositah; Nurmaranti Alim (Politeknik Pertanian Negeri Samarinda, 2025)
In order to achieve optimal production, oil palm plants necessitate adequate conditions that are in balance with the intended growth requirements and the land conditions of the environment in which these plants are grown. This study aims to determine the land suitability classfication and factors for oil palm plants in the Politani Samarinda oil palm experimental plantation. This study uses a quantitative descriptive methoddology based on in field observations and literature reviews. Data obtained from field observations and literature reviews is classified depending on land characteristics. The data grouping resulted are tabulated and compared with the growth growing requirements for oil palm plants. According to the results of the semi-detailed land suitability analysis for oil palm plants in the Politani Samarinda oil palm experimental plantation. The Politani Samarinda oil palm experimental plantation has limited land suitability (S3) with soil depth as the limiting factor of rooting media (rc).